InSAR-based monitoring and analysis of settlement in high-filled road embankment and slope in loess region - Wang, Limin; Chai, Shaoqiang; Sun, Liang; Liu, Liang; Ding, Wen (Frontiers in Earth Science, 2025)
The settlement behavior of high-filled road embankments and slopes in loess regions poses significant challenges to the safety and stability of engineering. The Interferometric Synthetic Aperture Radar (InSAR) technique was used to process the Sentinel-1A satellite data from 8 April 2021, to 9 May 2022. The spatiotemporal distribution characteristics of surface settlement were analyzed. The accuracy and reliability of the InSAR technology results were validated through comparison with actual measurement data, and the settlement behavior of the high-filled road after the completion of the pavement was further investigated. Results indicate that the most severe settlement occurred during the early post-construction phase, with maximum settlement rates reaching 32 mm/year and cumulative settlement peaking at 57 mm. These critical settlement zones located at the intersection of the road and the embankment slope and the south side of the embankment slope. Following the completion of the pavement, surface settlement stabilized to within 3 mm, indicating the structural safety and stability of the road. The results of finite element numerical simulation showed that the stability safety factor of the high-filled road embankment slope was 1.39, satisfying the safety limit requirements for slopes. The study demonstrated that InSAR technology can provide an effective technical means for the early identification of engineering hazard risks in loess regions, offering a basis for further monitoring, early warning, and scientific prevention.